Sex-Specific Association of Endogenous PCSK9 With Memory Function in Elderly Subjects at High Cardiovascular Risk - Simeone, Paola G.; Vadini, Francesco; Tripaldi, Romina; Liani, Rossella; Ciotti, Sonia; Di Castelnuovo, Augusto; Cipollone, Francesco; Santilli, Francesca (Frontiers in Aging Neuroscience, 2021)
Background: Growing evidence indicates that cognitive decline and cardiovascular diseases (CVDs) share common vascular risk factors. Protease proprotein convertase subtilisin/kexin type 9 (PCSK9) is associated with CV disease risk and has been also involved in neuronal differentiation. Aim: Evaluate whether in patients at high CV risk cognitive function is related to PCSK9 levels. Methods. One hundred sixty-six patients (67 female) were enrolled. A detailed neuropsychological (NP) assessment was performed. PCSK9 levels were measured with ELISA. Results: Men had significantly higher short-term memory, executive function, and praxic and mental representation skills, as reflected by Forward Digit Span (FDS) (p = 0.005), Trail Making Test-A (TMT-A) (p = 0.047), Clock Drawing Test (CDT) (0.016). Endogenous PCSK9 levels were higher in female (p = 0.005). On linear regression analysis PCSK9 predicts short term memory only in females (Beta = 0.408, p = 0.001), with an interaction between PCSK9 and gender (p = 0.004 for interaction PCSK9 by sex). The association of PCSK9 with FDS in female was partially mediated by waist circumference (mediation effect 8.5%). Conclusions: In patients at high CV risk short term memory was directly related to PCSK9 levels only in women, revealing the relevance of sex in this relationship. The association of PCSK9 with memory function may be mediated, at least in part, by waist circumference.